2009
DOI: 10.1016/j.jebo.2009.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of envy on relational employment contracts

Abstract: We study the effects of envy on relational employment contracts in a standard moral hazard setup with two agents. Performance is evaluated via an observable, but non-contractible signal which reflects an agent's individual contribution to firm value. Both agents exhibit horizontal disadvantageous inequity aversion. In contrast to the literature, we find that inequity aversion may be beneficial; in the presence of envy, for a certain range of interest rates, relational contracts may be more profitable. For some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…If the latter is the case, then it holds that rG¯<rI¯α for any α, and the above result indeed carries over to arbitrary variations in the agents' propensity for envy. Kragl and Schmid () provide a condition for which rI¯α in fact increases in α (see Proposition in that paper). Under that condition it must hold that rI¯αrG¯ is positive and increasing in α. Consequently, for a range of interest rates r with r̂α<rrI¯α and for any α, the principal clearly favors the individual bonus scheme over the group scheme.…”
Section: The Relational Contractsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the latter is the case, then it holds that rG¯<rI¯α for any α, and the above result indeed carries over to arbitrary variations in the agents' propensity for envy. Kragl and Schmid () provide a condition for which rI¯α in fact increases in α (see Proposition in that paper). Under that condition it must hold that rI¯αrG¯ is positive and increasing in α. Consequently, for a range of interest rates r with r̂α<rrI¯α and for any α, the principal clearly favors the individual bonus scheme over the group scheme.…”
Section: The Relational Contractsmentioning
confidence: 99%
“…As credibility issues do not arise in this case, I only consider the single‐period game. First, I will briefly characterize the principal‐agent problem with an individual bonus scheme, as analyzed by Kragl and Schmid (), and restate some of the main results as far as relevant for the subsequent analysis . Then, I will investigate the optimal contract with a group bonus scheme.…”
Section: The Contracts Under Verifiable Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Second, as another outcome of the consideration of an equal pay norm, the relative advantages of TBC compared to RPE increase. Previous studies have similarly shown that social preferences on the part of the agents can lead to lowerpowered incentives (Neilson and Stowe 2010;Kragl and Schmid 2009;Englmaier and Wambach 2010;Bartling and von Siemens 2010a) and increase the merits of TBC as compared to RPE (Itoh 2004;Grund and Sliwka 2007;Sandner 2009). Although the underlying reasoning is comparable, our approach is different, as it is not based on agents comparing their remunerations.…”
Section: Introductionmentioning
confidence: 95%
“…Fehr and Schmidt [9] illustrated the powerful impact of fairness concerns on cooperation, competition, incentives, and contract design. Kragl and Schmid [10] found that inequity aversion may be beneficial for that relational contracts may be more profitable to a certain extent. Eliashberg [11] analyzed competitive decision-making situations in terms of their preference structures and posterior performance, through a Bayesian decision-theoretic framework.…”
Section: Introductionmentioning
confidence: 99%